Do Managerial Ability Impact Indonesian Firm Risk-Taking Behavior? - Emiliya Rahma Wati; Heru Tjaraka; Erina Sudaryati (AKRUAL: JURNAL AKUNTANSI, 2020)
This study aims to examine the role of managerial in firm decisions. This study recognizes that managerial plays an important role in corporate decision making. Decisions carried out by the company are not only influenced by the manager's explicit mandate to maximize firm value, but also by the manager's ability to manage the company. In previous research it was found that high-ability and low-ability managers have opposite effects on firm behavior and firm value. High-ability managers accept risk-taking whereas low-ability managers refrain from taking risks. Managerial Ability in this study was measured using DEA (Data Envelopment Analysis) while for firm risk-taking behavior using the return on assets (ROA), return on equity (ROE), and research and development costs to total assets (R&D). The model used in this study is a causality model or the relationship of influence between research variables. The proposed model is analyzed using the Structural Equation Model (SEM) causality technique. This research was conducted on manufacturing companies listed on IDX (Indonesian Stock Exchange) in 2013-2017. However, unlike previous studies, the results of this study indicate that highly capable managers play a role in minimizing corporate risk taking. This research contributes as a reference for Indonesian corporate investors and also regulators as a reflection of the effectiveness of regulations made in Indonesia.